The tactical method of encirclment in the millitary operations of Zahriddin Muhammad Bobur - Dotsent D.T. Аrtikbayev; podpolkovnik J.S. Qobilov; professor A.Sh.Ziyadullayev (Global Scientific Publishing, 2023)
This article describes a tactical way “Tulgama” developed by armed Babur.
Keywords: Tulgama; Amir Temur; tactical